Attitudes towards people with intellectual disability in the UK and Libya: A cross-cultural comparison. (April 2016) - Benomir, Aisha M.; Nicolson, Roderick I.; Beail, Nigel
Abstract: Background: The attitude of the general population towards people with intellectual disability (ID) provides important background for policy development. Furthermore, because of changes in attitudes across cultures, it is vital to ground policy development for each country in data from that country. Aims: This paper aimed to undertake a cross-cultural study, investigating attitudes to people with ID in Libya in the year 2011, and to compare the Libyan data with those for the UK. Methods and procedures: This paper provides a cross-cultural analysis of attitudes to people with ID, using a questionnaire study of three groups in Libya and in the UK: science students, psychology students and professionals in ID support. The questionnaire used was the established Community Living Attitude Scales for Mental Retardation (CLAS-MR). Outcomes and results: In terms of the four CLAS-MR sub-scales, the Libyan sample showed significantly less favourable scores on Empowerment, Similarity and Exclusion than the UK sample, but no significant difference on the Sheltering sub-scale. Within-country analysis indicated no main effects of gender on all four sub-scales in Libya and the UK. Conclusions: This study is the first to undertake quantitative analysis of attitudes to people with ID in Libya. The attitudes were in general less favourable than in the UK and other Western countries, but showed similarities with studies of attitudes to people with ID in Pakistan.